Community of Practice of Promotoras de Salud to address health inequities during and beyond the COVID-19 pandemic - Rodriguez Espinosa, Patricia; Martinez Mulet, Yessica; Chen, Wei-ting; Kirk, Cary; Tran, Cindy; Gonzalez, Mike; Rosas, Lisa G.; , Promotoras Con Stanford En Acción (Frontiers in Public Health, 2023)
Using principles of Community-Based Participatory Research, we describe a community of practice for community health workers and promotoras (CHW/Ps) to address COVID-19 inequities in the Latinx community. We offer a concrete example of how programs can engage CHW/Ps as full partners in the research process, and how programs can support CHW/Ps' capacity and workforce development during implementation. We conducted four focus groups with CHW/Ps (n=31) to understand needs and invited 15 participants to the community of practice to work on issues identified by the group. We examined impact according to number of community members reached, types of outreach activities, surveys, and online views of educational materials. Process evaluation involved two focus groups with seven organizations and a Ripple Effects Mapping session with the CHW/Ps. Our community of practice has built CHW/Ps' capacity via 31 workshop and co-created culturally and linguistically relevant COVID-19 materials that have reached over 40,000 community members and over 3 million people online. The community of practice proved effective in supporting CHW/Ps to address COVID-19 inequities in the Latinx community. Our evaluations demonstrated benefits for community-academic partnerships, for CHW/Ps, and for the community. This model represents an innovative workforce training model to address health inequities and can be applied to other health topics.